Oral and anal carriage of Neisseria meningitidis among sexually active HIV-infected men who have sex with men in Denmark 2014–15. (April 2021) - Tinggaard, Michaela; Slotved, Hans-Christian; Fuursted, Kurt; Rosenstierne, Maiken Worsøe; Kronborg, Gitte; Lebech, Anne-Mette; Thorsteinsson, Kristina; Katzenstein, Terese L.; Storgaard, Merete; Holden, Inge Kristine; Johansen, Isik Somuncu; Benfield, Thomas
Highlights: The carriage rate of Neisseria meningitidis was 32% among HIV infected MSM. Meningococci were detected in both oral and anal samples. Non-groupable meningococci were most prevalent, followed by genogroup B. Results support that sexual transmission of meningococci can occur. Abstract: Introduction: Outbreaks of invasive meningococcal disease (IMD) among men who have sex with men (MSM) caused by a hypervirulent, non-encapsulated Neisseria meningitidis (Nm) clone belonging to genogroup C have been described. We aimed to determine the oral and anal carriage rates and genogroups of Nm among MSM living with HIV. Methods: Sexually active MSM living with HIV were included. A questionnaire, an oral wash sample and an anal swab were collected at baseline and 12 months follow-up. Identification of Nm and genogrouping was performed using real-time polymerase chain reaction analysis. Results: Among 82 MSM, the Nm carriage rate was 31.7% (95% CI 21.9–42.9) at baseline. The oral carriage rate was 24.4% (95% CI 15.6–35.1) and the anal rate was 11.0% (95% CI 5.1–19.8). Non-groupable Nm were most prevalent followed by genogroup B and genogroup Y. Rates were similar at follow-up. Conclusion: Strains of Nm were detected in both oral washes and anal samples in our study. Our results suggest that Nm may be transmitted sexually among MSM. Non-groupable Nm were predominant in our population and no genogroup C Nm were detected.